TEACHER TRAINING AND INNOVATIVE PRACTICES: PATHS TO TRANSFORMATIVE EDUCATION - de Sousa, Enielen Silva; Botelho, Janete Rodrigues; de Sousa Pantoja, Silvana; de Oliveira, Mara Rita Duarte; Sardinha, Marinilda Corrêa; da Silva, Benedita das Graças Sardinha; Souza, Alexandre Augusto Cals; Albuquerque, Roseli Moraes Cardoso (Seven Editora, 2025)
The article, titled "Teacher Training and Innovative Pedagogical Practices: Paths to Transformative Education," aims to analyze how teacher training can enhance innovative pedagogical practices and, consequently, pave the way for transformative education that promotes student autonomy, creativity, and active participation in the learning process. To this end, the study is based on a bibliographic survey, mobilizing theoretical frameworks that discuss the complexity of teaching, the importance of continuing education, and the need for innovative pedagogical practices, such as those of Paulo Freire (2019), António Nóvoa (2009), Selma Garrido Pimenta (2012), and Maurice Tardif (2014). The study indicates that teacher training, when conceived as a continuous and critical process, can foster innovative pedagogical practices centered on active student participation, collaborative work, and the problematization of reality. The article’s scope is that critical teacher training, grounded in solid theoretical foundations and an ethical-political commitment to the emancipation of the individual, constitutes an indispensable path to implementing innovative pedagogical practices that contribute to the construction of a democratic, humanizing, and transformative education. DOI: https://doi.org/10.56238/sevened2025.030-070